Analisis Faktor dan Upaya Pencegahan Unmet Need KB di Kota Padang - Erwani, Erwani; Susanti, Dewi; Yusefni, Elda; Faisal, Muhammad (LPPM Universitas Prima Nusantara Bukittinggi, 2023)
Background: Unmet needs for family Planning as an indicator of family planning program marketing is still low in West Sumatra, namely 1 and 3 provinces with the lowest coverage. In the city of Padang shows almost the same conditions. Padang City is one of the cities with a high number of unmet needs for family planning. The Municipal Government of Padang created the Kampung KB program as an innovative breakthrough that requires various supports for development. Community empowerment is very necessary for the success of KB villages.Purpose : This study aims to find the causes of unmet need for family planning and community empowerment to prevent unmet need for family planningMethods: This research is explorative qualitative research, data collection was carried out by means of in-depth interviews. The informants were PUS, family planning cadres, Kelurahan family planning program holders and heads of RT.Results: The results of the study found 5 factors causing family planning not to be fulfilled, namely knowledge, attitudes, access to information, religion and husband's support. The component of prevention efforts is by empowering the community to prevent unmet needs, namely the role of parents in preventing PSP based on the causal factors found, namely community awareness, improving attitudes regarding the importance of family planning programs, capacity building (providing knowledge and facilities), empowerment (making programs and authorization)Conclusion: Factors that cause unmet need for family planning are knowledge, attitudes, access to information, religion and husband's support. Prevention efforts, namely community empowerment, are one of the strategies that can be implemented to prevent unmet need, especially in the KB villages which are the government's priority programs. it caused an area with family planning problems higher.